2023
DOI: 10.1111/1365-2664.14375
|View full text |Cite
|
Sign up to set email alerts
|

Afforestation and abandonment of semi‐natural grasslands lead to biodiversity loss and a decline in ecosystem services and functions

Abstract: 1. During the past century, semi-natural grasslands, once widespread throughout Europe, have largely been converted into intensively managed agricultural areas, abandoned or afforested. These large-scale land-use changes have already resulted in considerable biodiversity loss but can also lead to decline in ecosystem service provision and ecosystem multifunctionality.2. We assessed the impact of afforestation and abandonment of semi-natural grasslands on the supply of ecosystem services in Western Estonia. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…The results are in line with related findings from the literature. Communities with higher biodiversity have been shown to be able to deliver ecosystem functions and services at a higher level [25,60], while biotic homogenisation in forests may have substantial negative impacts on their ecosystem services [59]. The correlations between forest condition and multifunctionality are stronger than those with individual ecosystem services (see Tables S2-S4), which is also in accordance with earlier results [106].…”
Section: The Relationship Between Multifunctionality and Ecosystem Co...supporting
confidence: 88%
See 2 more Smart Citations
“…The results are in line with related findings from the literature. Communities with higher biodiversity have been shown to be able to deliver ecosystem functions and services at a higher level [25,60], while biotic homogenisation in forests may have substantial negative impacts on their ecosystem services [59]. The correlations between forest condition and multifunctionality are stronger than those with individual ecosystem services (see Tables S2-S4), which is also in accordance with earlier results [106].…”
Section: The Relationship Between Multifunctionality and Ecosystem Co...supporting
confidence: 88%
“…Ecosystem condition can be described in many ways [57], and one of the most common is the use of biodiversity indicators [34,58]. Plant species richness and diversity are especially well-linked to the provision of multiple services and functions in forests and other ecosystems [25,46,59,60]. Forest structure and its connection to ecosystem services multifunctionality are less studied, especially on a large scale.…”
Section: Ecosystem Condition and Its Relations To Ecosystem Services ...mentioning
confidence: 99%
See 1 more Smart Citation
“…At the smallest spatial scale, we found losses in species richness much more drastic than suggested by previous studies based on relative changes and larger spatial scales. We found that species richness has decreased by almost 50% over the last 60 years at the plot level, a loss that has to be seen as alarming and may threaten fundamental ecosystem functions and services (Prangel et al, 2023). In contrast, species richness does not show significant changes at larger spatial scales, indicating that complete extinction of species at this scale has been relatively limited and/or effectively compensated for by the introduction of new, largely non-native, species and suggesting that it may still be possible to reverse the observed loss of biodiversity.…”
Section: Con Clus Ionmentioning
confidence: 87%
“…The contribution of biodiversity to ES provision is multi‐layered and complex, and the specific links between species richness and ES provision are unclear (Mace et al, 2012; Lavorel, 2013). However, although the link between biodiversity and ecosystem functioning has been debated, positive relations have been shown in a growing number of experiments and data syntheses (Hector & Bagchi, 2007; Tilman et al, 2006a, 2006b; Lefcheck et al, 2015; Prangel et al, 2023). For example, each individual service relies on several ecosystem functions and the degree of this dependency varies significantly among services (De Bello et al, 2010; Cardinale et al, 2012).…”
Section: Introductionmentioning
confidence: 99%